2021
DOI: 10.1039/d1em00048a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neighborhood air quality after idling of an urban oil production site

Abstract: Oil and gas development is occurring in urban, densely populated neighborhoods; however, the impacts of these operations on neighborhood air quality are not well characterized. In this research, we leveraged...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We did not observe a significant spatial gradient for the oil factor, suggesting that residents across the area may be impacted by the pollution source and that there may not be much of an exposure gradient within 1 km. Epidemiological studies have shown health effects for residents living within 1 km of oil and drilling sites, and several studies indicate increased air pollution and reduced health within 3 km. We observed the Mn and Ni factor to be highest in people who live in homes instead of apartments, which may have to do with exposure to soil. People in homes may have more soil exposure than people in apartments, and soil may be one of the main sources of metal exposure.…”
Section: Discussionmentioning
confidence: 63%
“…We did not observe a significant spatial gradient for the oil factor, suggesting that residents across the area may be impacted by the pollution source and that there may not be much of an exposure gradient within 1 km. Epidemiological studies have shown health effects for residents living within 1 km of oil and drilling sites, and several studies indicate increased air pollution and reduced health within 3 km. We observed the Mn and Ni factor to be highest in people who live in homes instead of apartments, which may have to do with exposure to soil. People in homes may have more soil exposure than people in apartments, and soil may be one of the main sources of metal exposure.…”
Section: Discussionmentioning
confidence: 63%
“…These source attribution efforts afford the relevant communities or agencies the ability to address hazards in order of importance. For instance, a previous PMF analysis near an oil and gas facility in Los Angeles resulted in VOCs split into 6 main factors, with compounds emanating from: combustion, aged motor vehicle emissions, fresh motor vehicle emissions, biogenic, industrial manufacturing, and natural gas [32]. This analysis aided in community understanding of anthropogenic and biogenic air quality risks in the area.…”
Section: Positive Matrix Factorizationmentioning
confidence: 99%